Lessons from the development and delivery of a rural suicide prevention program. (10th November 2021) - Handley, Tonelle E.; Davies, Kate; Booth, Angela; Dalton, Hazel; Perkins, David
Abstract: Aims: Suicide prevention remains a priority in rural and remote Australia, where suicide rates continue to be higher than those in urban communities. This commentary describes the Good SPACE suicide prevention program, and the lessons learned from delivering this program over a 14‐year period. Context: The Good SPACE program has been operating in rural New South Wales since 2007. The program focuses on educating rural community members to recognise the signs of suicide vulnerability, and how to take appropriate action if they encounter someone considering suicide. Approach: Communities are selected to receive Good SPACE training in consultation with key stakeholder organisations, or by request from communities. Across the life of the program, key challenges in its administration have included short‐term funding arrangements and staff turnover. Strengths have included the ability to adapt content to meet the needs of rural communities (eg from an initial focus on helping farmers during periods of drought, to a broader focus on all rural residents and a wider range of adversities). As the program moves forward, emphasis will be placed on harder‐to‐reach populations, including males and those with lower mental health literacy. Conclusion: The Good SPACE program has ongoing funding to adapt its content and continue administration through the Rural Adversity Mental Health Program (https://www.ramhp.com.au/ ). The lessons learned throughout the life of the program might be of use to other organisations aiming to provide community‐based education programs in rural and remote communities.